Electron conduction mechanism in indium oxide and its implications for amorphous transport - Hu, Yaoqiao; Cho, Kyeongjae (Frontiers in Materials, 2024)
The electron conduction mechanism in indium oxide (In2O3) and its implications for amorphous transport have been investigated from an orbital overlap perspective.Combined density functional theory and empirical tight binding modeling reveal that the electron transport is facilitated by the neighboring metal atomic s orbital overlap "without" oxygen's p-orbital involvement. In other words, the electron transport pathway in oxides is only due to the metal-metal medium range connection. This electron conduction mechanism is extended to amorphous In2O3 which unveils that the amorphous disorder influences the electron transport through impacting the metalmetal medium range order including metal-metal coordination number and metalmetal separation. Our results provide an insight into the current theoretical understanding of electron transport in amorphous oxide semiconductors.